A Comparative Study Of Register And Orientalist Thinking In Hafez’s Selected Translated Poems - Raveshi, Nazila (2018)
The present thesis embodies a comparative study of register and orientalist thinking in Hafez’s translated poems. Hafez’s poems appeal to many scholars because of their outstanding literary features. Three different translations done namely by Pazargadi, Clarke, and Bell of eight Hafez’s poems were selected for analysis. The selection was on the assumption that Clarke’s and Bell’s translations could be affected by orientalist thinking since both translators could be termed orientalists for having lived in the east for many years. Pazargadi, on the other hand, is a Muslim Iranian scholar who introduces Hafez as a real believer in God.